Ship Under-Keel Clearance Monitoring Using RTK GPS - Gourlay, Tim; Cray, W. (Coasts and Ports 'CD', 2009)
This article proposes a new method to assist with under-keel clearance (UKC) management, using realtime kinematic (RTK) GPS receivers. The proposed GPS method is intended to be integrated with existing UKC planning methods. The current state of the art in RTK GPS technology is discussed, and a method is outlined for using such measurements to monitor the clearance between a ship's keel and the sea floor.The method uses permanently installed GPS base stations in the area of interest, together with surveyed in GPS receivers on ships wishing to use the system. An example use of the method is given based on measurements taken in Torres Strait.